Nihilism and the Roots of Crisis in American Democracy: A Diagnosis of Cornel West - Jeliński, Julian (Journal of Education Culture and Society, 2020)
Cornel West’s diagnosis of the crisis of the American democracy is the subject matter of this article. Analyzing the condition of the American democracy of the end of XX and the beginning of XXI centuries, C. West focused on the individual, existential character of the crisis. The diagnosed state had according to him much affect not only on political issues, but first and foremost on the spread of nihilism among American citizens. Nihilism – is understood in the C. West as senselessness of life and low self-esteem is the subject matter of this article.